Career maturity and career guidance needs of Malay secondary school students - Jamaliah Abdul Rahim (2009)
The main purpose of this study was to assess the career maturity levels and career guidance needs of Malay secondary students in Singapore schools. This study also aimed to investigate the influence of age/grade level, gender, academic ability (stream of study), socioeconomic status (SES) and parental influence on the career maturity and career guidance needs of the students.